A case study of Proton - Kuppusami, Umadevi (2002)
This study describes PROTON's background and history, organizational structure, research and development, competitors and its overall performance throughout its establishment. Proton Edar Sdn Bhd and EON (Edaran Otomobil Nasional Berhad) have played a vital role in marketing PROTON cars. These two dealers adopted well-planned marketing strategies. One of strategies adopted by Proton Edar Sdn Bhd is by carrying out temporary "showrooms" which had been tremendously successful, contributing to an increase of 25% out of the total sales in 2001.